Dendritic Cells and Programmed Death-1 Blockade: A Joint Venture to Combat Cancer - Versteven, Maarten; Van den Bergh, Johan M. J.; Marcq, Elly; Smits, Evelien L. J.; Van Tendeloo, Viggo F. I.; Hobo, Willemijn; Lion, Eva (Frontiers in Immunology, 2018)
Two decades of clinical cancer research with dendritic cell (DC)-based vaccination have learned us that this type of personalized medicine is safe and has the capacity to improve survival, but as a monotherapy is unlikely to cure the cancer. Designed to empower the patient’s antitumor immunity, huge research efforts are set to improve the efficacy of next-generation DC vaccines and to find synergistic combinations with existing cancer therapies. Immune checkpoint approaches, aiming to breach immune suppression and evasion to reinforce antitumor immunity, have been a revelation in the immunotherapy field. Early success of therapeutic antibodies blocking the programmed death-1 (PD-1) pathway has sparked the development of novel inhibitors and combination therapies. Hence, merging immunoregulatory tumor-specific DC strategies with PD-1-targeted approaches is a promising path to explore. In this review, we focus on the role of PD-1-signaling in DC-mediated antitumor immunity. In the quest of exploiting the full potential of DC therapy, different strategies to leverage DC immunopotency by impeding PD 1-mediated immune regulation are discussed, including the most advanced research on targeted therapeutic antibodies, lessons learned from chemotherapy-induced immune activation and more recent developments with soluble molecules and gene-silencing techniques. An overview of DC/PD-1 immunotherapy combinations that are currently under preclinical and clinical investigation, substantiate the clinical potential of such combination strategies.